Hypermobile spectrum disorders symptoms in patients with functional neurological disorders and autism spectrum disorders: A preliminary study - Nisticò, Veronica; Iacono, Adriano; Goeta, Diana; Tedesco, Roberta; Giordano, Barbara; Faggioli, Raffaella; Priori, Alberto; Gambini, Orsola; Demartini, Benedetta (Frontiers in Psychiatry, 2022)
Autism Spectrum Disorders (ASDs) and Functional Neurological Disorders (FNDs) are two neuropsychiatric conditions sharing common features in terms of alexithymia, sensory sensitivity and interoceptive issues. Recent evidence shows that both the disorders present symptoms compatible with a diagnosis of hypermobile Ehlers-Danlos Syndrome and Hypermobile Spectrum Disorders (hEDS/HSD), a heterogeneous group of heritable connective tissue disorders characterized by joint hypermobility, skin hyperextensibility, and tissue fragility. Here we compared the prevalence of hEDS/HSD-related symptoms in patients with FNDs, individuals with ASDs without intellectual disabilities, and a group of neurotypical healthy controls (HN)/non-clinical comparison group (NC). Twenty patients with FNDs, twenty-seven individuals with ASDs without intellectual disabilities and twenty-six HNNC were recruited and completed the Self-reported screening questionnaire for the assessment of hEDS/HSD-related symptoms (SQ-CH). We found that 55% of the patients with FNDs, 44.4% of the individuals with ASDs and 30.8% of HNNC scored above the cut-off at the SQ-CH; SQ-CH scores of both FNDs and ASDs group were significantly higher than the HNNC group’s ones. In conclusion, both ASDs and FNDs individuals present hEDS/HSD-related symptoms in a higher number than the general population. Imputable mechanisms include (i) overwhelming of executive functions with consequent motor competence impairment for ASDs individuals, and (ii) exacerbation of FNDs symptoms by physical injury and chronic pain due to abnormal range of joint mobility. Moreover, we speculated that the amygdala and the anterior cingulate cortex circuitry might be responsible for the imbalances at the proprioceptive, interoceptive, and emotional levels.